Holding it All Together. Ancient and Modern Approaches to Joining, Repair and Consolidation - Laborde Marqueze, Ana (Ge-conservacion, 2011)
Reseña del libro:Holding it All Together. Ancient and Modern Approaches to Joining, Repair and Consolidation VV.AA. Editado por Janet Ambers, Catherine Higgitt, Lynne Harrison and David Saunders Archetype Publications in association with The Bristish Museum. London, 2009 210 páginas, ilustraciones y figuras,  29,6  x 21  cm. ISBN: 978-1-904982-47-D